Kombinasi ekstrak jeruk nipis dan madu dalam meningkatkan daya hambat Staphylococcus aureus - Fitriana Fitriana; Safridha Kemala Putri; Darmawati Darmawati (Politeknik Kesehatan Kemenkes Aceh, 2022)
Background: Staphylococcus aureus (S. aureus) is one of the bacteria that contribute to the occurrence of infectious diseases, such as mastitis, dermatitis, respiratory tract infections, and toxic shock syndrome. Therapy that can be given to patients with Staphylococcus aureus infection is antibiotics, but inappropriate antibiotics can cause resistance. Using herbal ingredients is an effort to deal with resistance due to the incompatibility of antibiotic administration. The essential herbal ingredients for therapy, namely lime extract (Citrus aurantifolia) and honey, have antibacterial substances such as flavonoids and essential oils.Objectives: The study aims to measure the combination of lime extract and honey in increasing the inhibition of Staphylococcus aureus bacteria.Methods: Experimental research using a combination of lime and honey extracts, single preparation of lime juice (Citrus aurantifolia), and single preparation of honey with concentrations of 100%, 75%, 50%, and 25%, as well as gentamycin antibiotics as positive control and NaCl 0,85% as a negative control. The research was conducted at the Microbiology Laboratory, Department of Medical Laboratory Technology, Aceh Health Polytechnic, Ministry of Health, in May 2021. The experimental method used in this study is the diffusion method. Data were obtained by observing the study's results of increasing the inhibition of the combination of lime juice and honey against the growth of Staphylococcus aureus bacteria. Data analysis by measuring the average diameter of the antimicrobial inhibition zone against the growth of Staphylococcus aureus bacteria.Results: The combination of lime extract and honey can form a more significant inhibition against the growth of Staphylococcus aureus compared to a single preparation of lime juice at concentrations of 100% and 75%. While at concentrations of 50% and 25%, no more significant inhibition was formed than in the single preparation.Conclusion: The combination of lime extract and honey can inhibit the growth of Staphylococcus aureus.